Encapsulation and subsequent freeze-drying of Lactobacillus reuteri CRL 1324 for its potential inclusion in vaginal probiotic formulations - Juárez Tomás, María Silvina (2015)
Probiotic formulations must include a high number of viable and active microorganisms. In this work, the survival of human vaginal Lactobacillus reuteri CRL 1324 during encapsulation, lyophilization and storage, and the activity of encapsulated and/or freeze-dried bacterial cells were evaluated. Extrusion-ionic gelation technique was applied to encapsulate L. reuteri CRL 1324, using xanthan and gellan. Encapsulated and free bacterial cells were freeze-dried with or without lactose and skim milk as lyoprotectors. The different systems obtained were stored at room temperature and at 4°C for 150 days. The following determinations were performed: L. reuteri CRL 1324 viability, microorganism released from capsules, survival in a medium simulating the vaginal fluid and maintenance of beneficial properties (growth inhibition of opportunistic pathogenic Streptococcus agalactiae NH 17 and biofilm formation). L. reuteri CRL 1324 encapsulation was efficient, allowing the recovery of a high number of entrapped lactobacilli. The survival of encapsulated L. reuteri during lyophilization and storage was significantly higher in the presence of lyoprotectors. At the end of storage, highest numbers of viable cells were obtained in free or encapsulated cells freeze-dried with lyoprotectors, stored at 4°C. Encapsulated and/or liophilized L. reuteri cells maintained their viability in simulated vaginal fluid as well as the ability to inhibit S. agalactiae NH 17 growth and to form biofilm. Encapsulated and freeze-dried L. reuteri CRL 1324 can be included in a suitable pharmaceutical form for vaginal application to prevent or treat urogenital infections in women.